Pengaruh Return on Assets, Ukuran Perusahaan, Debt to Equity Ratio, dan Total Asset Turnover Terhadap Nilai Perusahaan : Studi Empiris pada Perusahaan Sub Sektor Automobiles and Components yang Terdaftar di Bursa Efek Indonesia pada Periode 2019- 2023 - Ela Fitriningsih; Muhammad Jusman Syah (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This study aims to investigate the partial effects of Return On Assets, Firm Size, Debt To Equity Ratio, and Total Asset Turnover on Company Value in the Automobiles and Components sub-sector listed on the Indonesia Stock Exchange during the 2019-2023 period. The sample consists of 9 companies in the Automobiles and Components sub-sector listed on the Indonesia Stock Exchange during the same period. This study employed multiple linear regression analysis using SPSS version 25.0 and Microsoft Excel 2016. The results revealed that Return On Assets and Debt To Equity Ratio have a positive and significant partial effect on Company Value, while Firm Size has a negative and significant partial effect on Company Value. On the other hand, Total Asset Turnover has no partial effect on Company Value.